(3GdeSJXQa aj CNHGQ GdLhGQjs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO Hf ehSi GdgQGhj s)
(3ChdgG (B:s
(3gPG LRA SejJg GdeSJXQa aj CNHGQ GdLhGQj(B: (3CSeGA GdCfOdSjI s
(3BNQgG (B:s
(3hde JRd JHcjg hJfhM Ydjg MJi eGJJ BNQ eG hbaJ Ydjg ef GdeSJXQa aj CNHGQ GdLhGQj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdNW eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3HgG HYV GdJbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B59 s
Keywords: (3GdCOHs